Rancang Bangun Sistem Monitoring Karakteristik Solar Cell dan Peltier Berbasis Internet Of Thing: Design and Development Of Solar Cell and Peltier Characteristics System Base On Internet Of Thing - Murnis, Eko putra; bandria, sepannur (Institut Riset dan Publikasi Indonesia, 2023)
This IOT-based monitoring tool for the characteristics of solar cells and Peltier is a tool that is used as a comparison for solar cells and Peltier. with this tool, experiments can be carried out to determine the characteristics of solar cells and peltiers, with direct observation methods to collect data on sources of electrical energy that can be produced by solar cells and peltiers, Therefore, 3 experiments were carried out using a 2W/6V solar cell, Peltier TEG SP1848 and 3W/12V LEDs. The first was data collection of the electrical energy source produced by 2 solar cells, connected in series with an experimental length of 60 minutes and producing a voltage of 10, 39 V, 0.11 A current and 1.10 W power, the second experiment of data collection on a solar cell and Peltier series circuit with an experimental time of 60 minutes produces a voltage of 10.38 V, a current of 0.13 A and a power of 1.30 W In the third experiment, data collection on a series of solar cells and a parallel circuit on a Peltier with an experimental length of 60 minutes resulted in a voltage of 11.13 V, a current of 0.10 A and a power of 1.10 W. produces a voltage of 0.75 V better than a series circuit with a greater resistance and produces a voltage of 0.74 V better than a series circuit of 2 voltage solar cells with a temperature of each peltier 37? to 39 ? , with The level of decline is still stable when the solar cell is not exposed to sunlight and the lack of heat energy sources that can be absorbed by the Peltier, it can be said that peltier can help the effectiveness of solar cells. Keywords : PZEM-017 sensor DC, ESP8266, Blynk IOT